Solar panel for integrated irrigation system / Eka Lulu Khoirun Nisa ... [et al.] - Khoirun Nisa, Eka Lulu; Fransiska, Adelia; Kristoferin, Aulia Giga; Putera Agung, Muhammad Rasyid (2024)
Agriculture is a crucial sector in society for fulfilling food needs. However, there are numerous challenges faced in contemporary Indonesian agriculture. One of them is the El Nino climate phenomenon, which leads to a decrease in water availability for irrigation. Hence, innovative solutions are needed for agricultural irrigation while remaining environmentally friendly, utilizing solar panels that harness sunlight. Solar-powered irrigation is expected to meet the watering needs in the agricultural sector. This research will discuss the implementation of solar panels for agricultural irrigation systems to support agricultural productivity.